2009
DOI: 10.1016/j.mcn.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor regulates early postnatal developmental cell death of dopamine neurons of the substantia nigra in vivo

Abstract: Brain-derived neurotrophic factor (BDNF) was the first purified molecule identified to directly support the development of mesencephalic dopamine neurons. However, its physiologic role has remained unknown. Based on patterns of expression, it is unlikely to serve as a target-derived neurotrophic factor, but it may instead act locally in the mesencephalon, either released by afferent projections, or in autocrine fashion. To assess a possible local role, we blocked BDNF signaling in the substantia nigra (SN) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The secreted factors GDNF and BDNF and the transcription factor Pitx3 are individually required for the proper development of mdDA neurons or for their survival during postnatal and adult stages (Baquet et al, 2005;Smidt and Burbach, 2007;Pascual et al, 2008;Oo et al, 2009), but it remained unclear whether a regulatory interaction exists between these three factors during embryonic development or in the adult brain. Here we show that NF-B-mediated GDNF/Ret signaling is, at least in part, sufficient for the activation of Pitx3 expression, which is in turn required for the transcription of BDNF in a rostrolateral and medial mdDA neuronal subpopulation, thereby promoting the survival of these neurons during mouse embryonic development (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted factors GDNF and BDNF and the transcription factor Pitx3 are individually required for the proper development of mdDA neurons or for their survival during postnatal and adult stages (Baquet et al, 2005;Smidt and Burbach, 2007;Pascual et al, 2008;Oo et al, 2009), but it remained unclear whether a regulatory interaction exists between these three factors during embryonic development or in the adult brain. Here we show that NF-B-mediated GDNF/Ret signaling is, at least in part, sufficient for the activation of Pitx3 expression, which is in turn required for the transcription of BDNF in a rostrolateral and medial mdDA neuronal subpopulation, thereby promoting the survival of these neurons during mouse embryonic development (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the role of BDNF in dopaminergic systems, recent studies show that BDNF facilitates maturation of mesenchymal stem cell-derived dopamine progenitors to functional neurons (Trzaska et al 2009) and modulates cell death in the substantia nigra (Oo et al 2009). BDNF therefore seems to play a key role in the development of dopamine system in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Further, regulation of the DAergic development is mediated by other neurotrophic factors, including BDNF, 11 which promotes sprouting of DAergic axons and regulates plasticity of the DAergic neurons. 84 Studies also showed that psychostimulant-induced enhancement of DA transmission 35 and TH at the DAergic terminals mediated through NOS gene. 85 Moreover, NT-induced cell degeneration is thought to be involved in NT autoxidation and disruption of the cellular redox system.…”
Section: -64mentioning
confidence: 99%